Comparing Real-World Healthcare Costs Associated with Single-Tablet Regimens for HIV-1: The 2-Drug Regimen Dolutegravir/Lamivudine vs. Standard 3- or 4-Drug Regimens - Priest, Julie; Germain, Guillaume; Laliberté, François; Duh, Mei Sheng; Mahendran, Malena; Fakih, Iman; Oglesby, Alan (Infectious diseases and therapy, 2023)
Introduction Dolutegravir/lamivudine (DTG/3TC) is a 2-drug regimen for HIV-1 treatment with long-term efficacy and good tolerability comparable to 3- or 4-drug regimens. This study evaluated DTG/3TC cost versus other standard single-tablet regimens during its first year of approval. Methods This retrospective study analyzed US claims data from adults with HIV-1. Eligibility criteria included ≥ 1 dispensing of DTG/3TC, DTG/abacavir (ABC)/3TC, bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF), elvitegravir (EVG)/cobicistat (COBI)/FTC/TAF, and darunavir (DRV)/COBI/FTC/TAF (index date was first dispensing) and ≥ 6 months of continuous eligibility before index date (baseline period). All-cause and HIV-related healthcare costs were evaluated during the observation period (index date until earliest of end of continuous eligibility or data availability). Adjusted cost differences and adjusted cost ratios were estimated using multivariable regression models controlling for differences in baseline characteristics between cohorts. Results Overall, 22,061 individuals with HIV-1 and dispensed treatment with DTG/3TC ( n = 590), DTG/ABC/3TC ( n = 4355), BIC/FTC/TAF ( n = 9068), EVG/COBI/FTC/TAF ( n = 7081), or DRV/COBI/FTC/TAF ( n = 967) were included. Most claims data were from men (mean age ~ 46 years). Mean unadjusted all-cause total healthcare costs per patient per month were significantly lower for DTG/3TC versus BIC/FTC/TAF and DRV/COBI/FTC/TAF, and mean unadjusted HIV-related healthcare costs per patient per month were significantly lower for DTG/3TC versus DRV/COBI/FTC/TAF. Cost differences were primarily driven by significantly lower pharmacy costs for DTG/3TC versus other regimens ( P < 0.001), while medical costs were similar across cohorts. Results were similar among treatment-naive and treatment-experienced individuals. After adjusting for baseline covariates, significant adjusted cost differences were generally consistent with unadjusted findings. Adjusted cost ratios generally favored DTG/3TC for all-cause healthcare and HIV-related costs, with all pharmacy cost ratios favoring DTG/3TC ( P < 0.001). Conclusion Dolutegravir/lamivudine had the lowest healthcare costs of BIC/FTC/TAF, EVG/COBI/FTC/TAF, and DRV/COBI/FTC/TAF, and the lowest pharmacy costs of all regimens, in unadjusted and adjusted analyses and by treatment experience, supporting the economic benefits of DTG/3TC as an initial or switch regimen for HIV-1.